DEVELOPING THE CONCEPTUAL APPROACH TO STANDARDIZATION OF VOCATIONAL EDUCATION - V. I. Blinov; Y. Y. Yesenina (Russian State Vocational Pedagogical University, 2015)
The paper analyzes educational standards as the key concept of modern education; their interrelation with the national qualifications system and professional standards being considered. The authors denote the reasons for changing the conceptual approach to the standard developments, and demonstrate the possible ways of educational quality assurance.Diversification and mobility of the modern qualifications along with the fast technological changes affects the educational content and knowledge acquisition, and requires the variable and flexible educational  curricula and management. The global development trends, concerning the educational quality standards, involve their orientation on the learning outcomes, which should be taken into account while developing the Federal State Educational Standards of the fourth generation. The authors reveal the structure of the future standard, outline its implementation stages, and demonstrate the mechanism guaranteeing the regulatory legal provision of professional education.